2022
DOI: 10.3389/fnut.2022.847704
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Frequent Sugar-Sweetened Beverage Intake and Sleep Duration in School Children: A Cross-Sectional Study

Abstract: BackgroundHigher consumption of sugar-sweetened beverages (SSBs) maybe association with children's sleep pattern. However, few studies have considered this association in Asia, especially in school children. This study investigated the relationship between children's consumption frequency of such beverages and their sleep duration.MethodsParticipants aged 6–12 years were analyzed from two survey data in 2012 and 2013–2016 Nutrition and Health Surveys in Taiwan. A total of 2,628 participants were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Park et al determined that the consumption of energy drinks was higher among those who engaged in physical activity 7 or more times a week compared to those who did so twice a week or less (34) . Some studies have found that physical activity is associated with improved sleep quality (26)(27)(28)(29) and higher energy drink consumption (20)(21)(22)(23)(24) . However, we observed no evidence of an association between overall sleep quality and physical activity in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al determined that the consumption of energy drinks was higher among those who engaged in physical activity 7 or more times a week compared to those who did so twice a week or less (34) . Some studies have found that physical activity is associated with improved sleep quality (26)(27)(28)(29) and higher energy drink consumption (20)(21)(22)(23)(24) . However, we observed no evidence of an association between overall sleep quality and physical activity in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We performed multivariate logistic regression analysis to evaluate the association between poor sleep and higher amount of energy drink consumption as one model for all categories, and the results were reported as adjusted OR (aOR) and 95 % CI. Furthermore, sensitivity analysis, that is, multinomial logistic regression analysis (26) , was conducted to investigate the association between sleep and consumption amount of the energy drinks after classifying by adjusting the selected covariates. The differences were considered statistically significant level of P -value ( P < 0·05).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies conducted in Asia have reported more servings of daily SSBs consumption among children or adolescents with a sleep duration < 7 hours 11 as well as less hours of nocturnal sleep on weekdays and sleep debt in children with high frequencies of SSBs consumption 12 . On the basis of the literature, the correlations of SSBs consumption and sleep with the health of children can be further clari ed through analysis that combines both SSBs consumption and sleep.…”
Section: Introductionmentioning
confidence: 88%
“…Prolonged screen-based sedentary time is associated with increased SSB consumption and short sleep duration in adolescents (28,29). In addition, short sleep duration and increased SSB consumption are interrelated (30,31). Hence, they might form clustered lifestyle behaviors, which have neutralizing or synergistic effects in combination (32).…”
Section: Introductionmentioning
confidence: 99%